Effect of selective dorsal rhizotomy on bladder dysfunction in children with spastic cerebral palsy - Wenbin Jiang; Junlu Wang; Pierre A. Robe; Min Wei; Sen Li; Rui Wang; Qijia Zhan; Bo Xiao (Scientific Reports)
Abstract This study investigated the prevalence and severity of lower urinary tract symptoms (LUTS) in children with spastic cerebral palsy (SCP) and evaluated the effect of selective dorsal rhizotomy (SDR) in alleviating these symptoms. The study also explored the correlation between postoperative LUTS improvement and intraoperative electrophysiological findings. Prospective data were collected from a consecutive cohort of 247 children with SCP who underwent SDR and were retrospectively analyzed. Pre- and post-operative assessments included muscle tone, motor function, LUTS and intraoperative electrophysiology data were analyzed. Preoperatively, 94 patients (38.1%) had LUTS, and the severity of LUTS negatively correlated with motor function (R=-0.32, P < 0.0001). After SDR, muscle tone decreased, motor function improved (P < 0.0001), and LUTS resolved in 49/94 patients (52.1%). LUTS improvement correlated with a higher proportion of sensory nerves evoking anal sphincter EMG > 20µV. SDR effectively reduces spasticity, improves motor function, and alleviates LUTS in most children with SCP. Intraoperative neurophysiology may predict improvements, warranting further research.